Neuromarketing: Strategies for Visual Perception in Predicting Consumer Behavior (Tema Central) - Quisimalín Santamaría, Hernán Mauricio (2025)
The article explores consumers’ brain responses to specific visual stimuli to optimize marketing strategies and understand their behavior. Using eye-tracking techniques, it analyzes consumers’ reactions to beverage posts on Instagram. The research focuses on three areas of interest: Background (AOI 1), Packaging (AOI 2, including the label), and Linguistic Code (AOI 3), evaluating initial fixations (F1), the duration of the first fixation (F2), and the total number of fixations (F3). The analysis using an ANOVA table reveals that the packaging (AOI 2) initially captured attention (F1), maintained the longest fixation duration (F2), and recorded the highest total number of fixations (F3), with a p-value of 0, indicating a significant difference. The Tukey test shows no significant differences between the Background and the Linguistic Code among the three products evaluated. However, the packaging of the black tea is perceived distinctly compared to the mandarin and hibiscus flavors. These findings underscore the importance of packaging design in capturing and retaining consumer attention, highlighting significant differences in attention to various visual elements. The integration of these visual neuromarketing strategies enables companies to design persuasive user experiences, fostering consumer loyalty and sensory satisfaction.